Assessment of Macrobenthos Assemblages Along the Seabed Characteristic in the Cempi Bay, West Nusa Tenggara, Indonesia: A Case Study in the Dry Season - Fahlevy, Karizma; Sembiring, Agustinus; Kaessari Magenta, Rias; Iqbal Havis, Muchammad; Suroso, Adi; Nauval, Rahmat; P. H. Simanjuntak, Charles (HAYATI Journal of Biosciences, 2026)
The ecosystem in Cempi Bay, Indonesia, is known for its diverse coastal ecosystems. Gathering baseline data to understand the habitat and its fauna is essential. The study aims to update macrobenthos data and identify natural patterns across sediment gradients, specifically in the dry season. Cempi Bay has three distinct areas: the lower reach (open sea), the middle reach (mixing water), and the upper reach (influenced by freshwater). The most dominant classes in the macrobenthic assemblages were Gastropoda, Bivalvia, and Polychaeta, especially in the lower and middle reaches with sand and silty sand seabed textures. However, the upper reach area with sandy silt textures showed a different pattern of macrobenthic assemblages, with fewer classes, leaving only Gastropoda and Bivalvia. The feeding habits of macrobenthos also varied, with carnivores, deposit feeders, and suspension feeders dominating the lower and middle reach areas. It is important to continue monitoring macrobenthos to understand if these patterns are natural or caused by environmental changes.